Influence of the cooling conditions on the temperature and crystallinity profiles generated in a sisal fiber reinforced-polycaprolactone/starch molded part - Cyras, Viviana Paola (2004)
In this work, we performed the simulation of the temperature and relative degree of crystallinity developed across the thickness of a sisal fiber reinforced-polycaprolactone/starch (30%SF-PCL/S) molded part under different cooling conditions. The non-isothermal kinetic model of Kamal and Chu (13) was used to predict the degree of crystallinity profiles. In order to obtain the temperature profiles, the energy equation was solved by treating the composite as a continuum using mass averaged physical properties. The results indicated that for cooling at a constant wall temperature, gradient-less crystallinity profiles for a wall temperature of 283 K and thicknesses lower than 10 mm are obtained. On the other hand, when cooling at a constant cooling rate, paired degree of crystallinity pieces can be obtained only for thicknesses lower than 2 mm. The continuum numerical approach used herein has the ability of predicting the optimal cooling cycle for manufacturing thick and crystallinity gradientless SF-PCL/S parts © 2004 Society of Plastics Engineers.